-8-4x=3-7x

Simple and best practice solution for -8-4x=3-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-4x=3-7x equation:


Simplifying
-8 + -4x = 3 + -7x

Solving
-8 + -4x = 3 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-8 + -4x + 7x = 3 + -7x + 7x

Combine like terms: -4x + 7x = 3x
-8 + 3x = 3 + -7x + 7x

Combine like terms: -7x + 7x = 0
-8 + 3x = 3 + 0
-8 + 3x = 3

Add '8' to each side of the equation.
-8 + 8 + 3x = 3 + 8

Combine like terms: -8 + 8 = 0
0 + 3x = 3 + 8
3x = 3 + 8

Combine like terms: 3 + 8 = 11
3x = 11

Divide each side by '3'.
x = 3.666666667

Simplifying
x = 3.666666667

See similar equations:

| -8.4x=58.8 | | 7a+3=14 | | 2lx+2l=18 | | 5(7-2m)+5=90 | | 2x^2-8x+15=11 | | 45-x=7 | | -7(2b+1)+(15b-3)=0 | | (-5u^3v^4+9u)+(-5u^3v^4-8u+8u^2v^2)+(-8u^4v^2+8u^3v^4)= | | 1.4q-1.3-1.8q=-1.4q-2.8 | | 4x+23=12x-73 | | 3x+4=59 | | 12-3=10x+3 | | y+34=18 | | 7+2x^2+4x^2=37 | | 5(5x+13)=25 | | 9m+3(m+12)-2= | | 0.45x+.05(2-x)=.10(-55) | | 4x(1-3x)=0 | | 5x+2=-5x+12 | | y=x^2-4x-1 | | 7z-8z=8z-6+4z | | 6w+13=3w-26 | | 3(2x+3)-5= | | -7(1)(-7)= | | 8x=18+5x | | 8x-2=40x+6 | | 3(5x+7)=-48+9 | | 48-x=7-4x | | 2a+6+9a+8= | | 10x-(3x-11)=25 | | x+4=59 | | 9x(x-5)=20x^2-46X |

Equations solver categories